Effect of impaired kidney function on outcomes and treatment effects of oral anticoagulant regimes in patients with atrial fibrillation in a real-world registry - Salbach, Christian; Milles, Barbara Ruth; Hund, Hauke; Biener, Moritz; Müller-Hennessen, Matthias; Frey, Norbert; Katus, Hugo; Giannitsis, Evangelos; Yildirim, Mustafa (PLOS ONE, 2024)
Background - The impact of impaired kidney function on outcomes and treatment benefits of vitamin-K antagonists (VKA) versus direct oral anticoagulants (DOAC) in patients with atrial fibrillation (AF) has insufficiently been investigated in randomized controlled studies (RCTs). Most studies and registries are either biased due to incomplete enrolment of consecutive patients in large pharma industry sponsored registries, or due to short recruitment periods or incomplete assessment of important variables in national registries. - Methods - This study uses data from the Heidelberg Registry of Atrial Fibrillation (HERA-FIB), a retrospective single-center registry of 10,222 consecutive patients with AF presenting to the emergency department of University Hospital of Heidelberg from June 2009 until March 2020. Rates of all-cause mortality, stroke, major bleeding and myocardial infarction (MI) were related to the presence and severity of impaired presenting kidney function, as well as to assigned treatment with VKA vs. DOAC. - Results - The risks for all-cause mortality (HR: 3.26, p<0.001), stroke (HR: 1.58, p<0.001), major bleeding (HR: 2.28, p<0.001) and MI (HR: 2.48, p<0.001) were significantly higher in patients with an eGFR<60 ml/min at admission and increased with decreasing eGFR. After adjustment for variables of CHA2DS2VASc-score, presence of eGFR <60 ml/min remained as an independent predictor for all-cause mortality, major bleeding and MI. The hazard ratio (HR) for all-cause mortality, major bleedings and MI was significantly lower in patients receiving DOAC compared to VKA. - Conclusion - Findings from our large real-life registry confirm the data from RCTs and extend our knowledge on the effectiveness and safety of DOACs to subjects that were underrepresented in RCTs.